DETERMINANTS OF E-COMMERCE ADOPTION AMONG SMALL AND MEDIUM ENTERPRISES IN NORTH SUMATRA PROVINCE: THE ROLE OF TECHNOLOGY READINESS AND PERCEIVED BENEFITS - Pius Deski Manalu; Aidil Putra (Journal of Global Business and Management Review, 2025)
This study investigates the determinants of e-commerce adoption among Micro, Small, and Medium-sized Enterprises (MSMEs) in North Sumatra Province, Indonesia, emphasizing the roles of technology readiness and perceived benefits. Using a quantitative approach, data were collected from 384 MSME respondents through a structured survey and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results reveal that perceived benefits have a significant positive effect on e-commerce adoption (β = 1.578, t = 5.519, p < 0.001), while technology readiness shows a significant negative effect (β = –1.025, t = 3.543, p < 0.001). The model’s explanatory power is strong, with R² = 0.642, indicating that 64.2% of the variance in adoption is explained by these two variables. The findings highlight that MSMEs are more motivated to adopt e-commerce when they clearly perceive its tangible advantages, such as increased operational efficiency, broader market reach, and higher sales, rather than solely relying on technological readiness. This paradox suggests that infrastructure alone does not guarantee adoption without adequate digital literacy and trust in online transactions. Policymakers should therefore prioritize programs that enhance digital capabilities and demonstrate practical benefits to strengthen e-commerce adoption among MSMEs.